Spread of tumor microenvironment contributes to colonic obstruction through subperitoneal fibroblast activation in colon cancer. Issue 4 (19th March 2015) - Yokota, Mitsuru; Kojima, Motohiro; Higuchi, Youichi; Nishizawa, Yuji; Kobayashi, Akihiro; Ito, Masaaki; Saito, Norio; Ochiai, Atsushi
Abstract : We evaluated the influence of the cancer microenvironment formed by peritoneal invasion (CMPI) on clinical findings in colon cancer patients. In addition to the association with poor prognosis, we discovered a relationship with bowel obstruction. Detailed analysis revealed that clinical findings related to bowel obstruction occurred more frequently in patients with an elevated type tumor, which had peritoneal elastic laminal elevation to the tumor surface, compared to those with non‐elevated type tumors among those with elastic laminal invasion (ELI). Lateral tumor spread and increase of tumor annularity rate in ELI‐positive elevated type cases suggested the morphological progression from ELI‐positive non‐elevated type to elevated type. In addition, α‐smooth muscle actin expression was the highest in ELI‐positive elevated type, and prominent expressions were found not only in the deep tumor area but also in the shallow tumor area. Furthermore, contraction assays revealed the robust contractile ability of subperitoneal fibroblasts stimulated by cancer cell‐conditioned medium. Our findings suggest that CMPI spread into the luminal side of the colonic wall along with tumor progression, which caused bowel obstruction through the activation of subperitoneal fibroblasts. However, although the clinical outcome was not different between the two types, the clinical findings were affected by the spread of CMPI. We are the first to explore how the alteration of the tumor‐promoting microenvironment, along with tumor progression, contributes to the development of clinical findings. Abstract : The cancer microenvironment formed by peritoneal invasion (CMPI) of colon cancer spread into the luminal side of the colonic wall, which caused bowel obstruction through the activation of subperitoneal fibroblasts. The formation of CMPI led to a poor prognosis, and furthermore, the spread of CMPI contributed to clinical developments related to bowel obstruction. We are the first to explore the alteration of the tumor microenvironment over the course of tumor progression and the influence this had on physical findings.